Vitalité des activités et rationalité du Lean : deux études de cas - Tahar-Hakim Benchekroun; Justine Arnoud; Rebecca Arama (Perspectives Interdisciplinaires sur le Travail et la Santé)
Lean Manufacturing (LM), inspired by the Toyota Production System, has spread throughout the automotive sector in France over the past twenty years – and from there, gradually, to all sectors of the economy. Requests for ergonomic interventions in Lean-type organizations have become more numerous, leading ergonomists to question the paradoxical position they find themselves in this type of work organization and to further their understanding thereof. This is likewise the goal of the present paper, which capitalizes on two studies conducted in different Lean systems in order to discuss LM and its paradoxes. The paper relies on a shared methodology combining two approaches – ergonomic work analysis and case study methodology – in order to understand what is at play within the work situations we encountered. Results suggest the existence of three separate approaches to LM. Each of these approaches is defended by different stakeholders who rarely communicate with one another and, indeed, often ignore each other’s approaches: at the top administrative level, there is the “strategic” LM, whose core principles are seemingly written in stone; the second level considers LM as it is “implemented” by middle management, who must rationalize the work force, etc., and produce indicators; and, finally there is the LM level that is “managed” day to day by work teams. The main transformation proposed in our research involved organizing meetings, discussions, and debates between these three stakeholders, while keeping the focus on the daily work activity.